PENGARUH JENIS ELEKTRODA TERHADAP POWER DENSITY PADA MICROBIAL FUEL CELL DENGAN PENAMBAHAN GRANULAR ACTIVATED CARBON - Vidia Wahyu Meidy Safitri; Tuhu Agung Rachmanto (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2020)
ABSTRACT Tofu liquid waste contains high organic content with a COD concentration of 1408 mg / l, TSS 191 mg / l and pH 4.46. One of the researches related to waste and energy utilization is Microbial Fuel cell (MFC). Chemical energy organic compounds from microorganism will be converted into electrical energy by the catalytic reaction of microorganism in anaerobic conditions is a process of microbial fuel cells. One of the challenges to developing an MFC system is to choose the right electrodes. The electrodes used must have high electrical conductivity, a wide surface, non-corrosive, biocompatible, stable. This study aims to find out the most optimum type of electrode in producing power density with variations of carbon graphite, zinc and copper, variations of 0, 48, 96, 144, and 192 hours. The pre-treatment are Coagulation-flocculation. The results showed that MFC with carbon graphite and carbon graphite electrodes produced a power density of 2292,994 mW/m2. MFC also reduces COD concentrations up to 88%. Processing time can affect the efficiency of COD removal. Keywords: Tofu Liquid Waste, Microbial Fuel Cells, power density